ANALISIS KOMPETENSI PEDAGOGIK GURU OTOMATISASI TATA KELOLA PERKANTORAN - Sirajuddin Saleh; Wirda Mustafa; Muhammad Darwis; Sulmiah Sulmiah (Universitas Khairun, 2023)
The role of the teacher in achieving the goals of Indonesian independence can be proven by the presence of a teacher figure in learning that cannot be replaced by any media and learning resources. This research is a quantitative descriptive research that aims to find out how the pedagogical competence of teachers majoring in Office Management Automation (OTKP) at SMKN 1 Bone. The total population in this study was 305 respondents with a sample of 152 respondents using a sampling technique that is Simple Random Sampling. Data collection techniques used are observation, questionnaires and documentation. The data analysis technique used is distribution analysis. The results of the study show that the pedagogical competence of teachers majoring in office management automation (OTKP) at SMKN 1 Bone is classified as very good in terms of characteristic indicators, learning theories and principles, curriculum, educational learning, potential, communication, learning process. , assessment and evaluation, and reflective action.